2015
DOI: 10.1590/s1806-92902015000700003
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical characteristics and fatty acid profile of meat from lambs with different genotypes and diets

Abstract: -The objective of this study was to evaluate the chemical composition and fatty acid profile of meat from Santa Inês, Dorper × Santa Inês, and undefined-breed lambs finished in a feedlot system according to two forage:concentrate ratios (50:50 and 20:80) in the diet. Overall, 54 non-castrated animals were used (with an average initial weight of 23±1.5 kg at 150 days old) and were slaughtered when they reached 36 kg of live weight or 63 days of confinement. Diets with high concentrate levels favored meat produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
3
9
1
3
Order By: Relevance
“…Values of desirable fatty acids (DFA) in the lamb meat reported by Madruga et al (2008), Coutinho et al (2014) and Costa et al (2015) ranged from 67 % to 84 % and were lower than the value observed in the present study (95 %). The DFA, which has been suggested as an indicator of dietary risk for cardiovascular disease, was useful when assessing meat quality (Costa et al, 2015). The ω6/ω3 ratio from the present study is in line with that recommended (4:1) by the World Health Organization (2003) and may be beneficial in human diets.…”
Section: Fatty Acid Profile Levels Of Replacementcontrasting
confidence: 95%
See 2 more Smart Citations
“…Values of desirable fatty acids (DFA) in the lamb meat reported by Madruga et al (2008), Coutinho et al (2014) and Costa et al (2015) ranged from 67 % to 84 % and were lower than the value observed in the present study (95 %). The DFA, which has been suggested as an indicator of dietary risk for cardiovascular disease, was useful when assessing meat quality (Costa et al, 2015). The ω6/ω3 ratio from the present study is in line with that recommended (4:1) by the World Health Organization (2003) and may be beneficial in human diets.…”
Section: Fatty Acid Profile Levels Of Replacementcontrasting
confidence: 95%
“…The MUFA and PUFA values were lower than reported by Madruga et al (2008) and Costa et al (2015). Different feeding systems may produce varied concentrations of UFA in meat due to higher levels of certain UFA or because the differences in the way the food was fermented in the rumen (Wood et al, 2008).…”
Section: Fatty Acid Profile Levels Of Replacementmentioning
confidence: 63%
See 1 more Smart Citation
“…When comparing these values with the literature, they are more than twofold higher than Costa et al (2015) reported for Brazilian lambs (0.45 vs. 0.60 g 100 g −1 FAME, P < 0.05) fed on a diet comprising 20 : 80 and 50 : 50 ratios of forage/concentrate, and slaughtered at live weight of 36 kg. Regarding individual monounsaturated FAs (MUFA), a lower (P < 0.001) proportion of oleic acid (OA) was found in P lambs (24.49 g 100 g −1 FAME) compared with S lambs (28.37 g 100 g −1 FAME).…”
Section: Effect Of Production Systemmentioning
confidence: 53%
“…On the other hand, product B with lamb declared as its main animal-derived component, had very low content of linoleic acid (C18:2; LA), typical for FA profile of this meat [29]. It seems plausible that the declared inclusion of …”
Section: Fatty Acid Contentmentioning
confidence: 95%